Correction of gummy smile: A report of two cases - Sarita Narayan; T V Narayan; P C Jacob (Wolters Kluwer Medknow Publications, 2011)
Cosmetically acceptable smiles show a gingival display of up to 3 mm. Gingival display of greater than 3 mm results in a gummy smile which is often unsightly for the individual and correction is sought. There are a variety of procedures used for surgical crown lengthening. Here, we describe two such cases requiring two different approaches for surgical crown lengthening.